Adaptation Practices of Young Central Asian Migrants in Tatarstan: A Socioanthropological Survey - Tatiana A. Titova; Vadim E. Kozlov; Elena V. Frolova (Oriental Studies)
Introduction. The Republic of Tatarstan is a key immigrant-recipient region of the Russian Federation. As of 2022, Tatarstan ranked first in Volga Federal District and fourth nationwide on the number of arrived migrants. One of the main reasons behind the situation is that according to annual socioeconomic reports by the Agency of Strategic Initiatives, Tatarstan sustainably holds leading positions of investment attractiveness. And it is already common practice that the majority of arriving individuals are Central Asian citizens, the three leading origin countries being Uzbekistan, Tajikistan, and Kyrgyzstan. The recent thirty years have witnessed a significant structural shift determined by that most newcomers never lived in the once unified state ― Soviet Union. Different strategies of sovereign sociocultural development adopted by currently independent countries of Central Asia have led to increased cultural distances between their citizens and Russia’s natives. Goals. The work attempts an analysis of how young Central Asian migrants adapt to new sociocultural conditions of Tatarstan’s polyethnic community. To facilitate this, the paper shall characterize the specifics of interaction between the former and locals, including some features of their language behavior. Materials and methods. Outcomes of the September-to-November 2023 survey held in Tatarstan constitute a source base for our analysis. The tested informants are ethnic Uzbeks, Tajiks, and Kyrgyzes. Qualitative research methodology and that of in-depth interviews have proven most instrumental herein. Results. The study reveals certain features of adaptation strategies and linguistic competence levels in ethnic and demographic groups of migrants. Special attention is paid to economic and sociopsychological reasons why the latter have chosen Tatarstan as their destination region, to indicators of cultural distances between locals and aliens. Conclusions. An important circumstance behind the choice of Tatarstan ― in the eyes of the respondents ― is the cultural and linguistic proximity, as well as the low level of ethnocentric attitudes on behalf of the host population. The article classifies and describes groups with maximum and minimum levels of linguistic competency, discusses some implied reasons. So, it is intention to reside in Tatarstan in the long term that essentially contributes to the successful acquisition and use of the Russian language.